2001
DOI: 10.1057/9780230502697
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Life-Style in the Twentieth Century

Abstract: Any person who does any unauthorised act in relation to this publication may be liable to criminal prosecution and civil claims for damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
23

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 0 publications
1
28
0
23
Order By: Relevance
“…For instance, in the Nordic countries up to 80 % of the disease burden had been prevented by the early 1990s, even though increased incidence was anticipated due to sexual life-style changes favouring spread of HPVs (Haavio-Mannila et al, 2001;Anttila et al, 1999;Vizcaino et al, 2000). In fact, an increase in the incidence of cervical adenocarcinoma, which is not prevented by the screening, was found among fertile-aged women (Vizcaino et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the Nordic countries up to 80 % of the disease burden had been prevented by the early 1990s, even though increased incidence was anticipated due to sexual life-style changes favouring spread of HPVs (Haavio-Mannila et al, 2001;Anttila et al, 1999;Vizcaino et al, 2000). In fact, an increase in the incidence of cervical adenocarcinoma, which is not prevented by the screening, was found among fertile-aged women (Vizcaino et al, 2000).…”
mentioning
confidence: 99%
“…A series of detailed questionnaire studies has revealed that sexual behaviour of 18-34-year-old Finnish women changed considerably from 1971 to 1999 (Haavio-Mannila et al, 2001). The number of lifetime sexual partners increased from 2?6 to 7?7 and the age of sexual debut decreased from 18?9 to 16?6 years, increasing the impact of oncogenic HPV infections due to earlier exposure.…”
mentioning
confidence: 99%
“…We found also some evidence suggesting that respondents were slightly more experienced regarding the number of lifetime partners than were those of the same age in a national survey based on a random sample (Haavio-Mannila & Kontula 2001). HaavioMannila and Kontula (2001), for example, found that 19% of females at the age of 18-34 years had had one sex partner in their lifetime, 28% of females 2-4 partners, 29% of females 5-9 and 23% of females 10 or more partners, whereas in our sample those numbers were 11%, 20%, 36% and 43%, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…No obstante, según diversos autores (Bozon, 2001;Connell, 2002; HaavioMannila, Kontula & Rotkirch, 2002;Inglehart & Baker, 2000;Weeks, 1993), la llegada de transformaciones socioculturales globales habría contribuido a modificar progresivamente las normas y valores de las sociedades occidentales en el sentido de un mayor individualismo, equidad en las relaciones entre géneros y un aumento de los valores seculares y auto-expresivos (Barrientos, 2003). Estas mutaciones sociales y culturales están generando: (a) una progresiva secularización del sexo, (b) una liberalización de las actitudes sexuales y un mayor énfasis en los derechos sexuales, (c) un incremento de la diversidad de las formas de vida doméstica y (d) una orientación de la sexualidad hacia el hedonismo, el placer y la recreación (Christopher & Sprecher, 2000;Haavio-Mannila et al, 2002).…”
Section: Los Cambios Socioculturales En El Mundo Occidental Y En Chileunclassified
“…No obstante, según diversos autores (Bozon, 2001;Connell, 2002; HaavioMannila, Kontula & Rotkirch, 2002;Inglehart & Baker, 2000;Weeks, 1993), la llegada de transformaciones socioculturales globales habría contribuido a modificar progresivamente las normas y valores de las sociedades occidentales en el sentido de un mayor individualismo, equidad en las relaciones entre géneros y un aumento de los valores seculares y auto-expresivos (Barrientos, 2003). Estas mutaciones sociales y culturales están generando: (a) una progresiva secularización del sexo, (b) una liberalización de las actitudes sexuales y un mayor énfasis en los derechos sexuales, (c) un incremento de la diversidad de las formas de vida doméstica y (d) una orientación de la sexualidad hacia el hedonismo, el placer y la recreación (Christopher & Sprecher, 2000;Haavio-Mannila et al, 2002).Sin embargo, persiste un conjunto de inequidades que afectan las relaciones de género y que en América Latina son sostenidas por el machismo y el marianismo (Cianelli, Ferrer & Jaime Barrientos Delgado y Manuel Cárdenas Castro, Escuela de Psicología, Universidad Católica del Norte, Antofagasta, Chile.Este artículo forma parte del Proyecto FONDECYT 1110423 "Homofobia y efectos psicosociales en la calidad de vida de homosexuales en Chile: hacia un modelo comprensivo".La correspondencia relativa a este artículo debe ser dirigida a …”
unclassified